Learning in personal and professional situations - Robert J. McKenna; Gary J. Conti; Robert A. Fellenz (Adult Education Research Conference, 1994)
The purpose of this study was to investigate the influences of personal and professional learning situations of the utilization of real-life learning strategies. Measurements using the Self-Knowledge Inventory of Lifelong Learning (SKILLS) indicated that Wyoming school administrators differed in four strategy areas in relationship to the strategies they used in personal and professional situations. Metacognition skills were used in both areas, and demographic variables were not related to learning strategy use. Results indicate that learning strategy usage is contextual and that SKILLS can be adapted for specific situations.